Monday

April 21, 2014

April 21, 2014

Posted by **joey** on Sunday, February 15, 2009 at 9:05pm.

when i try f(g(x)) = x and g(f(x)) = x to show that the two functions are inverses it doesn't work because i am not left with x when i solve the equation....

much help is needed thansk

- CALCULUS -
**bobpursley**, Sunday, February 15, 2009 at 9:21pmThey must not be inverse functions.

f(x)=x^2-1

y+1=x^2

x= +- root (y+1)

g(x)=+-root (x+1)

lets try the + root

f(g)=(x+1)-1=x

g(f)=+root (X^2-1+1)=x

- CALCULUS -
**joey**, Sunday, February 15, 2009 at 10:44pmwhere did you get the (x+1) from??

**Related Questions**

algebra - use the inequality -4t-8 is less than or equal to 12 a. t is greater ...

physics - A beam of electrons with momentum p=10^-23 kg m/s passed through a ...

Calculus - F(x) = 1-x and g(x) = 1/x These functions have the property that f = ...

Intermediate Algebra - Find the maximum value of the objective function and the ...

math - State the null hypothesis, Ho, and the alternative hypothesis, Ha, that ...

Algebra--Correction? - Solve x^2 -3x is greater than or equal to 10 Would the ...

Algebra - Did I do this correctly? 13 - (2c + 2) >(pretend it has the line ...

Algebra - Use a graphing calculator or a computer to graph the system of ...

math - solv the inequality: 1. 7-3x [is less than or equal to] 22 ---> x [is ...

Algebra 116 A - solve and graph 2x+9 greater or equal to 5 and 2x-13 greater or ...